2010
DOI: 10.1111/j.1600-0404.2009.01263.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of rivastigmine in patients with cognitive impairment no dementia because of cerebrovascular disease

Abstract: Narasimhalu K, Effendy S, Sim CH, Lee JM, Chen I, Hia SB, Xue HL, Corrales MP, Chang HM, Wong MC, Chen CP, Tan EK. A randomized controlled trial of rivastigmine in patients with cognitive impairment no dementia because of cerebrovascular disease. 
Acta Neurol Scand: 2010: 121: 217–224.
© 2009 The Authors Journal compilation © 2009 Blackwell Munksgaard. Objectives –  The safety and efficacy of early acetylcholinesterase inhibitors therapy in patients with cognitive impairment no dementia (CIND) after a cerebrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 20 publications
0
38
0
2
Order By: Relevance
“…11,38 Neither of those reviews found any significant improvements in cognition, and both reviews found significantly more harms associated with these agents. The most recent Cochrane review included 9 studies, 11 3 of which were excluded from our review because they included mixed patient populations with vascular dementia 39,40 or did not include our outcomes of interest. 41 Conversely, we included 3 studies that were not included in the recent Cochrane review.…”
Section: Discussionmentioning
confidence: 99%
“…11,38 Neither of those reviews found any significant improvements in cognition, and both reviews found significantly more harms associated with these agents. The most recent Cochrane review included 9 studies, 11 3 of which were excluded from our review because they included mixed patient populations with vascular dementia 39,40 or did not include our outcomes of interest. 41 Conversely, we included 3 studies that were not included in the recent Cochrane review.…”
Section: Discussionmentioning
confidence: 99%
“…135 The benefits of memantine and rivastigmine in vascular cognitive impairment are less well established. [137][138][139][140] A treatment-responsive form of nonhemorrhagic CAA is spontaneous CAA-related vascular inflammation. The CAA-related inflammation occurs in a distinct subgroup of patients with CAA in response to the vascular A deposits and is characterized by diffuse WMH on brain MRI attributed to vasogenic edema, seizures, and cognitive decline.…”
Section: Treatmentmentioning
confidence: 99%
“…105 Thus, AChEI have been shown to be effective and safe for the treatment of cognitive symptoms in vascular dementia. However, no AChEI has been licensed for the treatment of vascular dementia due to concerns as to the aetiological heterogeneity of patients included in the trials as well as lack of consistent effects on domains other than cognition.…”
mentioning
confidence: 99%